Morphogenesis of fruit as a subject matter for the carpological studies - Odintsova, A.V. (Ukrajinʹskyj botanic̆nyj z̆urnal, 2022)
In this review, the concept of fruit morphogenesis is treated in the context of implementation of the evo-devo approach in carpology. A new viewpoint on the fruit morphogenesis is proposed and justified, comprising the pre-anthetic, as well as post-anthetic periods of fruit development, id est, development of the gynoecium, and development of the fruit itself. It is proposed to recognize ontogenetical (individual) and evolutionary (historical) aspects of fruit morphogenesis, the first of them we can study directly, while the second aspect can be only hypothesized or treated as a theoretical model of fruit evolution in consequence of some presumed changes in the individual fruit morphogenesis. In this article these aspects are named as "ontomorphogenesis" and "phylomorphogenesis" of the fruit, correspondingly. Our concept of ontomorphogenesis of the fruit involves four components that could not be brought together, such as changes in the morphological structure of the gynoecium, abscission of the extragynecial floral parts and the style, histogenesis of the fruit wall and other fruit parts, and terminal stages of the fruit morphogenesis (dehiscence, splitting, or abscission). The current state of studies of these components in the individual and evolutionary contexts is discussed. By examining the patterns of fruit evolution, we should consider factors acting at both the post-anthetic and pre-anthetic periods of fruit ontomorphogenesis.